Global and Regional Impacts of the Clean Development Mechanism - Shunli Wang; Henri L.F. de Groot; Peter Nijkamp; Erik T. Verhoef (Tinbergen Institute, 2009)
Climate change is a serious concern worldwide. Policy research on climate change in the past decades has largely focused on applied modelling exercises. However, the implications of specific policy strategies such as the clean development mechanism (CDM) for global and regional economic and environmental developments has received relatively little attention. This is partly caused by the complexities of modelling an instrument like CDM. By using and modifying the GTAP-E modelling system, this paper sets out to trace the combined economic and environmental impacts of CDM policies. Particular emphasis is placed on technology transfer induced by alternative CDM policies. Specific attention is devoted to the possible negative consequences of non-participation of the USA in the global coalition, and the associated distributional impacts world-wide.
Keywords: F18; O13; Q54; Q56; 330; Climate Change; Clean Development Mechanism; Regional Development; Klimawandel; Clean Development Mechanism; Makroökonomischer Einfluss; Nachhaltige Entwicklung; USA; EU-Staaten; Welt